Potatoes Ilandoe' s / Muhammad Amir Syafiq Zuraimi ... [et al.] - Zuraimi, Muhammad Amir Syafiq; Shahril, Muhammad Shazwan; Ahmad Nazri, Ahmad Syazli; Yunus, Muhammad Zahierrurrahman (2017)
Differ from other competitor. The only restaurant specialize in potatoes dishes. To open up our own shop so that people will be easier to enjoy potato dishes. Our restaurant will stay on the long run and our name will be known domestically and internationally. To establish Potatoes Ilandos as the most unforgettable memories and enjoyable foods in Malaysia and to be the quickest service restaurant experience. To be the favourite choices and places for people looking to enjoy potatoes meals and dishes and create unforgettable taste. To serve high quality foods with great tastes. To provide the best quality of customer service. To offer quick and efficient products at affordable and reasonable price.